Gimmick! Vol. 1 - Kanari, Yōzaburō (VIZ Media, 2008)
Trouble with the wrong side of the law? Paparazzi won't leave you alone? Found yourself in a tight spot and you don't know where to go? Then it's time to get in touch with Kohei Nagase and his friends at Studio Gimmick. A prodigy in the realm of makeup and special effects, Kohei has got the skills to make sure that the people you don't want recognizing you won't. Things get rolling for Kohei and his stuntman sidekick Kannazuki when a sexy young starlet asks for their help in ditching her sleazy manager. Later, Kohei is commissioned to replace some zombies at a local horror theme park, but can he also prevent a disgruntled make-up artist from blowing the attraction sky high? And an actress whose reputation was sidelined by an accident that left her body scarred hopes Kohei can get her career back on track.